Food Safety as a contributor to Food Security: global policy concerns & challenges - Chattu, Vijay Kumar (Indian Journal of Community Health, 2015)
The theme for World Health Day campaign for this year 2015 is “Food safety: from farm to plate, make food safe”. The day focuses on demonstrating the importance of food safety along the whole length of the food chain in a globalized world, from production and transport, to preparation and consumption (1). Everyone needs food and needs it every day either plant sources or animal sources or both. The food we eat must be nutritious and safe but we often ignore or overlook the issue of food safety. Many cases of food borne diseases either acute poisoning or chronic exposure are largely under reported. In this globalized world, though the food chain extends over thousands of miles from different continents, an error or contamination in one country can affect the health of consumers on the other part of the world. To ensure full impact, these actions must build on principles of government stewardship, engagement of civil society, (2). According to UN, access to a safe and secure food supply is a basic human right. Food safety and food security are interrelated concepts which have an impact on the health outcomes and quality of human lives. As per Food and Agricultural Organization (FAO), Food security is a situation that exists when all people, at all times, have physical, social and economic access to sufficient, safe and nutritious food that meets their dietary needs and food preferences for an active and healthy life, (3). Based on the definition of Food security, four food security dimensions can be identified: food availability, economic and physical access to food, food utilization and stability over time. Apart from that food security is also affected by Poverty and Climate change. Food safety is an umbrella term that encompasses many aspects like food items handling, preparation and storage of food to prevent illness and injury. The other important issues are chemical, microphysical and microbiological aspects of food safety, (4). Control of allergens which can be life threatening to some people that are highly sensitive is the priority of food chemical control. Other chemical properties of food such as vitamin and mineral content are also important and affect the overall quality of the food but are not as significant in terms of food safety. Microphysical particles such as glass and metal can be hazardous and cause serious injury to consumers. Pathogenic bacteria, viruses and toxins produced by microorganisms are all possible contaminants of food and impact food safety. Like food security, food safety is also effected by poverty and climate change. Hence Foo